Performance and kinematics of various throwing techniques in team-handball - Wagner, H.; Pfusterschmied, J.; von Duvillard, S. P.; Müller, E. (Journal of Sports Science & Medicine, 2011)
In team-handball competition, the players utilize various throwing techniques that differ in the lower body movements (with and without run-up or jump). These different lower body movements influence changes in the upper body movements and thus also affect the performance. A comprehensive analysis of 3D-kinematics of team-handball throws that may explain these differences in performance is lacking. Consequently, the purpose of this study was (1) to compare performance (ball velocity and throwing accuracy) between the jump throw, standing throw with and without run-up, and the pivot throw; (2) to calculate the influence of kinematic parameters to ball velocity; and (3) to determine if these four throwing techniques differ significantly in kinematics. Three-dimensional kinematic data (angles, angular velocities and their timing, ball velocity and velocity of the center of mass) of 14 elite team-handball players were measured using an 8 camera Vicon MX13 motion capture system (Vicon, Oxford, UK), at 250 Hz. Significant difference was found between the four throwing techniques for ball velocity (p < 0. 001), maximal velocity of the center of mass in goal-directed movement (p < 0.001), and 15 additional kinematic variables (p < 0.003). Ball velocity was significant impacted by the run-up and the pelvis and trunk movements. Depending on floor contact (standing vs. jump throws), elite players in the study used two different strategies (lead leg braces the body vs. opposed leg movements during flight) to accelerate the pelvis and trunk to yield differences in ball velocity. However, these players were able to utilize the throwing arm similarly in all four throwing techniques.